Let's talk about sex: older people's views on the recognition of sexuality and sexual health in the health‐care setting. (8th October 2015) - Bauer, Michael; Haesler, Emily; Fetherstonhaugh, Deirdre
Abstract: Objective: To report on the findings of a systematic review which examined the experiences and views of older people aged 65 years and over on health professionals' recognition of sexuality and sexual health and whether these aspects of the person are incorporated into care. Review methods: The review followed the methods laid out by the Joanna Briggs Institute. Eleven electronic databases were searched using the terms sexual*, aged, ageing/aging, attitudes and care in any health‐care setting. Only quantitative and qualitative research and opinion papers written in English and offering unique commentary published between January 2004 and January 2015 were eligible. Results: A total of 999 papers were initially identified and of these, 148 were assessed by two reviewers. Eighteen studies – seven quantitative, eight qualitative and three opinion papers – met the inclusion criteria and were appraised. The importance of sexuality to well‐being, language used, expressing sexuality, discomfort discussing sexuality, inadequate sexuality health education and treatment and deficient communication with health‐care professionals were all identified as significant issues in a range of settings. Fourteen categories and five syntheses summarize the 43 findings. Conclusions: Sexuality remains important for many older people; however, embarrassment, dissatisfaction with treatment, negative attitudes and seeming disinterest by health professionals can all inhibit discussions. Professionals and health‐care services need to adopt strategies and demonstrate characteristics which create environments that are more supportive of sexuality. Issues related to sexuality and sexual health should be able to be discussed without anxiety or discomfort so that older people receive optimal care and treatment.